To Be Charged Again: Spotting of Fake News by Televion Stations in Kenya - Kabucua , John; Nyakundi , Nyamboga; Nguri , Matu (African Journal of Education,Science and Technology (AJEST), 2021)
Fake news is a major threat to credibility, trust, and speed of real news owing to its ability to spread fast, camouflage real news, spur ethnic conflicts, sabotage businesses and mislead voters. While there is empirical evidence that dissemination of fake news on social media and enactments of anti-fake news laws are on the rise globally, most of the empirical studies on fake news continue to focus on its political impacts and presence on social media. News television stations work under the premise of trust, credibility and speed now threatened by fake news hence the need to explore how they spot it. The specific research question was: How do news television stations in Kenya spot fake news?. The Gate keeping theory aided conceptualization of this study. The study adapted a relativist-constructivist/interpretivist philosophical paradigm hence qualitative approach and multiple case study method. The target population comprised of reporters and editors. A sample size of 16 participants from two television stations was selected using purposive sampling technique. Data was generated through in depth interviews and observations. Data was analysed thematically and presented in narrative form based on themes. The findings show that television stations spot fake news through counterchecking and verification, instinct, delays, online reverse search, calling the source, evaluating source’s credibility, chains of gate keepers, and editorial social media groups. Despite the numerous spotting practices fake news had permeated and aired on television resulting in court charges, fines, apologies and sacking of journalists. This study concludes that practices of spotting fake news by television stations in Kenya are incoherent, informal and weakly anchored on policy documents thus insufficient. Therefore, recommends that editorial boards establish standard and well documented practices for spotting fake news to arrest its growing threat to trust in news and journalism.